The influence of career development and work engagement on organization citizenship behavior mediated by organizational commitment - Dustiawatul Hasanah; Retno Purwani Setyaningrum (Institute of Computer Science (IOCS), 2024)
The aim of this research is to determine the influence of career development and work engagement on Organizational Citizenship Behavior which is mediated by organizational commitment of millennial generation employees manufacturing companies in Kawasan Industri MM2100. The method used in this research is quantitative, the data sources used are primary data from both questionnaire results and survey or journal data. The sampling technique uses the Lemeshow formula, and sampling in this research was carried out by distributing questionnaires with a sample size of 100 respondents. The analysis technique used in this research is multiple linear regression analysis technique using SMARTPLS version 3.0. The results of this research show that (1) the career development variable does not have a significant influence on Organizational Citizenship Behavior. (2) The work engagement variable has a significant influence on Organizational Citizenship Behavior. (3) The organizational commitment variable has a significant influence on Organizational Citizenship Behavior. (4) The career development variable has no significant influence on organizational commitment. (5) The work engagement variable has a significant influence on organizational commitment. (6) Career development mediated by organizational commitment has no significant influence on Organizational Citizenship Behavior. (7) Work engagement mediated by organizational commitment has a significant influence on Organizational Citizenship Behavior.